STUDI KOMPARATIF PENGUKURAN KINERJA PERUSAHAAN TERDIVERSIFIKASI DENGAN METODE EVA DAN MVA - RUSTAMADJI, RONY (Jurnal Akuntansi AKUNESA, 2016)
Corporate Diversification is one of managers choice to improve their firms’ performance. This study analyze firms’ performance of diversified company with Economic Value Added (EVA) and Market Value Added (MVA) in a sample of 47 firms’ from year 2013 to 2014. EVA and MVA have benefits than financial ratio measures because EVA and MVA method calculated cost of capital from the company and market value. Result of this study found that average EVA and MVA value of diversified company has positive. Positive value indicate that company success to improve their performance through diversification strategy.